2021
DOI: 10.3390/foods10040839
|View full text |Cite
|
Sign up to set email alerts
|

Potential Health Benefits of Plant Food-Derived Bioactive Components: An Overview

Abstract: Plant foods are consumed worldwide due to their immense energy density and nutritive value. Their consumption has been following an increasing trend due to several metabolic disorders linked to non-vegetarian diets. In addition to their nutritive value, plant foods contain several bioactive constituents that have been shown to possess health-promoting properties. Plant-derived bioactive compounds, such as biologically active proteins, polyphenols, phytosterols, biogenic amines, carotenoids, etc., have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
191
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(193 citation statements)
references
References 115 publications
0
191
0
2
Order By: Relevance
“…Plant foods are consumed globally as a source of minerals, vitamins, fiber, and other health-promoting compounds, and their consumption is recognized to decrease the risk of metabolic disorders, chronic conditions, and non-communicable diseases [ 1 , 2 ],. Among others, plant-based foods reduce the risk of diabetes, cancer, and cardiovascular diseases [ 3 , 4 ] because, in addition to micro- and macronutrients, they contain many bioactive components such as flavanols, carotenoids, and anthocyanins which have been shown to have health-promoting properties. Phenolic compounds are the most abundant secondary metabolites in plants, accumulating in all tissues and organs, and are at the center of research due to their antioxidant, anti-hypertensive, anti-inflammatory, and anti-carcinogenic effects [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant foods are consumed globally as a source of minerals, vitamins, fiber, and other health-promoting compounds, and their consumption is recognized to decrease the risk of metabolic disorders, chronic conditions, and non-communicable diseases [ 1 , 2 ],. Among others, plant-based foods reduce the risk of diabetes, cancer, and cardiovascular diseases [ 3 , 4 ] because, in addition to micro- and macronutrients, they contain many bioactive components such as flavanols, carotenoids, and anthocyanins which have been shown to have health-promoting properties. Phenolic compounds are the most abundant secondary metabolites in plants, accumulating in all tissues and organs, and are at the center of research due to their antioxidant, anti-hypertensive, anti-inflammatory, and anti-carcinogenic effects [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data mean that the oat protein will have a higher application prospect than other plant proteins. Oat bioactive peptides have been proved to have a good antioxidant activity ( 8 ), and hypotensive and hypoglycemic activities ( 15 , 16 ). Karas et al ( 17 ) also found that oat peptides are structurally similar to epidermal cell growth factor (EGF), which could be easily absorbed by the skin, and then improve skin metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in medicine and nutrition is shifting the traditional healthcare approach towards precision medicine, which prioritizes diseases’ prevention and health promotion mainly through lifestyle and diet-based approaches [ 3 ]. In this context, plant-derived antioxidants, such as flavonoids, vitamins, hormones, phenolic acids, and esters, are considered bioactive dietary compounds able to reduce oxidative stress and have been associated with several health benefits [ 4 ]. There is therefore a growing trend in consumer preferences towards natural antioxidants and in the industrial use of antioxidant-rich plant extracts in food and beverage formulations.…”
Section: Introductionmentioning
confidence: 99%